2022
DOI: 10.1021/acs.inorgchem.2c00081
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Thermodynamic, and Transport Properties of the Small-Gap Two-Dimensional Metal–Organic Kagomé Materials Cu3(hexaiminobenzene)2 and Ni3(hexaiminobenzene)2

Abstract: Metal–organic frameworks (MOFs) provide exceptional chemical tunability and have recently been demonstrated to exhibit electrical conductivity and related functional electronic properties. The kagomé lattice is a fruitful source of novel physical states of matter, including the quantum spin liquid (in insulators) and Dirac fermions (in metals). Small-bandgap kagomé materials have the potential to bridge quantum spin liquid states and exhibit phenomena such as superconductivity but remain exceptionally rare. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Both exhibit paramagnetism above 150 K and large negative Curie temperatures, suggesting antiferromagnetic (AFM) coupling of the Cu ions. 27 This conclusion is also supported by the X-ray magnetic circular dichroism (XMCD) spectra (Figure 3f and S11b), and agrees with our DFT calculations, i.e., the intralayer Cu ions are ferromagnetically (FM) coupled but interlayer AFM as ground states. At the same time, the liquid oxygen spoor was detected around 52 K, suggesting that oxygen had not been entirely eliminated from the samples.…”
Section: Resultssupporting
confidence: 87%
“…Both exhibit paramagnetism above 150 K and large negative Curie temperatures, suggesting antiferromagnetic (AFM) coupling of the Cu ions. 27 This conclusion is also supported by the X-ray magnetic circular dichroism (XMCD) spectra (Figure 3f and S11b), and agrees with our DFT calculations, i.e., the intralayer Cu ions are ferromagnetically (FM) coupled but interlayer AFM as ground states. At the same time, the liquid oxygen spoor was detected around 52 K, suggesting that oxygen had not been entirely eliminated from the samples.…”
Section: Resultssupporting
confidence: 87%
“…On the one hand, the Cu 3 (HHTP) 2 system has the potential to emerge as an archetypical QSL candidate in the domain of 2D MOFs, and on the other hand, magnetic frustration in 2D MOFs like Cu 3 (HIB) 2 and Ni 3 (HIB) 2 (HIB = hexaiminobenzene) is being assigned to structural disorders . Therefore, our observation on the robust magnetic frustration in bimetallic Cu x Zn 3– x (HHTP) 2 ( x = 1, 1.5, and 2) systems down to 5 K is intriguing and anticipated to be useful for chemically designing a wide variety of possible MOF-based QSL candidates.…”
Section: Resultsmentioning
confidence: 91%
“…On the other hand, disorders suppress spin ordering in 2D MOFs as in ET salts. Berry et al 234 reported paramagnetic behaviors in Ni 3 (HIB) 2 and Cu 3 (HIB) 2 (HIB is hexaiminobenzene). While no signals of spin freezing were detected in these MOFs with high θ / T order values over 10, which satisfied the frustration condition, the origin of the order absence was attributed to their stacking faults.…”
Section: Quantum Spin Liquidsmentioning
confidence: 99%